Mortality, morbidity and developmental outcome after ultrasound-dated preterm birth in a rural sub-saharan african setting. (4th April 2011) - Gladstone, M J; White, S A; Kafulafula, G; Neilson, J; Van den Broek, N
Abstract : Aims: We aimed to assess post neonatal survival, morbidity, growth and development at 12, 18 and 24 months in a community-based sample of infants born after spontaneous preterm delivery in rural Sub-Saharan Africa, all whom had gestational age accurately documented using ultrasound scanning. Methods: This was a community based stratified cohort study of post neonatal infants born in a rural Sub-Saharan African setting. Mothers had been recruited to a trial of antibiotic prophylaxis during pregnancy. Gestational age at delivery was based on ultrasound measurement of fetal bi-parietal diameter in early-mid pregnancy. 247 infants born before 37 completed weeks gestation and a random sample of 593 infants born at term were assessed at 12, 18 or 24 months of age. Outcomes assessed included survival (death), morbidity (reported by carer, admission or out-patient attendance and reasons for this and occurrence of seizures), growth (weight and height measurements) and development (Ten Question Questionnaire and Malawi Developmental Assessment Tool). Findings: Infants born prematurely were at significantly greater risk of death than those born at term (hazard ratio 1.79 95% CI (1.09 to 2.95) with twins included in analysis). Assessment of reported morbidity showed no differences between the groups (visits to the health centre (93%) and admissions to hospital (22%)). At follow-up, surviving premature infants were significantly more likely than term-born infants to have weight for age Z (WAZ) scores <−2 or −3SD as well as weight for length (WLZ) Z scores <−2 SD (p<0.05). There were significantly more preterm infants who scored positively on the Ten Question Questionnaire (p=0.002) and also significantly more children failing the MDAT at 18 months (p=0.011). Conclusions: Current international focus has been on interventions to address the high burden of neonatal mortality in the immediate newborn period. For babies born preterm who survive, a renewed interest in the post-natal period is needed, particularly as they demonstrate delays in growth and development. The major priority in perinatal medicine worldwide is to prevent preterm labour and birth. Our findings indicate that interventions in early childhood need to be tested to improve the outcome for preterm babies who otherwise carry long term disadvantage.